KOMUNIKASI PASTORAL BERBASIS KEPEMIMPINAN YESUS SEBAGAI FONDASI LOYALITAS JEMAAT MASA KINI - Agustinus Tomassawa; Jeliani Paliling; Lewiwanto Jalla; Triwanti Patasik (Adisam Publisher, 2026)
This study aims to analyze pastoral communication patterns based on Jesus's leadership model and to reveal their relationship with the formation of contemporary congregational loyalty. The problem addressed stems from the reality that many church members leave not because they have lost their faith, but because they feel unheard and distant from their leaders. This study employs a qualitative method using a literature review approach, collecting and analyzing theological sources, academic journals, and relevant sociological studies. Data were analyzed descriptively-analytically to construct a synthesis between Christian leadership theory, pastoral communication, and congregational loyalty concepts. The findings indicate that pastoral communication rooted in Jesus's leadership model, namely humanistic, relational, and servant communication, proves to be a decisive foundation for congregational attachment to the church. Leadership that fails to listen and remain relationally present emerges as the primary push factor driving church membership migration. This study affirms that contemporary churches need to reconstruct their pastoral communication model based on Jesus's example as the Good Shepherd so that congregational loyalty can be formed and sustainably maintained.